1981
DOI: 10.1002/macp.1981.021820612
|View full text |Cite
|
Sign up to set email alerts
|

On the salt‐linkage formations of porous and nonporous silica particles with trimethylammonium glycol chitosan iodide

Abstract: The stoichiometry of the salt-linkage formations of nonporous and porous silica particles with trimethylammonium glycol chitosan iodide (TGCI) was investigated by comparing the results of colloid titration and adsorption experiments with those of potentiometric titrations.The surface charge (Q) of colloidal silica as function of pH was evaluated by means of the colloid titration with TGCI. On the other hand, the density (0) of = SiOo groups of silica gel at different pH was also evaluated by the adsorption exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…To further investigate the stoichiometry of salt-linkage formation, the pH dependence of Ap was compared with that of D. The result for PDDA is shown in Figure 2, together with that for TGCI, already reported. 15 It is found that at pH > 6 a fair correlation between Ap and D is Figure 3. Adsorption isotherm of PDDA(nf) on colloid silica from 0.2 N NaCl solution.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To further investigate the stoichiometry of salt-linkage formation, the pH dependence of Ap was compared with that of D. The result for PDDA is shown in Figure 2, together with that for TGCI, already reported. 15 It is found that at pH > 6 a fair correlation between Ap and D is Figure 3. Adsorption isotherm of PDDA(nf) on colloid silica from 0.2 N NaCl solution.…”
Section: Resultsmentioning
confidence: 97%
“…The curve of Ap vs. pH (O) for PDDA(nf) was obtained from the adsorption experiments in the absence of salt under the conditions of Ca = 2 g/L and C{ -1 X 10"4-1 X 10~3 mol/L, while that (•) for TGCI was cited from ref 15. The D vs. pH curve (full line) was determined by the potentiometric titration with NaOH for colloid silica suspended into 1 N NaCl solution (see ref15).…”
mentioning
confidence: 99%
“…Even if the formal charges of a protein in a salt solution can be determined using appropriate approaches such as potentiometric titration and electrophoresis, ,, , the data obtained may not be identical with the number of protein charges responsible for the formation of an intrapolymer PPC. The reason is that PPC formation promotes the dissociation of counterions and/or protons; for example, and/or In fact, it has been demonstrated that the dissociation of counterions and/or protons occurs not only in the formation of PPCs 3,5,11,18 but also in the formation of salt linkages between oppositely charged polyions and colloid particles. Therefore, the present study focused on finding a key to understanding the detailed mechanism of PPC formation using a salt-free system.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have employed the conductometric method for examining the stoichiometry of PEC formation; for example, see refs and as reviews and refs as original papers in which the stoichiometry was studied at a certain ratio of [∼A − X + ] to [∼C + Y − ] or vice versa such as the end point of colloid titration, and over a wide range of [∼A − X + ]/[∼C + Y − ] or vice versa. However, we should note that (i) the PEC obtained from a polyanion−polycation mixture with a ratio of [∼A − X + ]/[∼C + Y − ] = 1 is a 1:1 stoichiometric complex when [∼A − X + ] = [X + ] and [∼C + Y − ] = [Y − ] can be observed, but (ii) at the ratios of [∼A − X + ]/[∼C + Y − ] ≠ 1 it is not clear whether the PEC formed is stoichiometric or nonstoichiometric even though [∼A − X + ] = [X + ] at [∼A − X + ] < [∼C + Y − ] or [∼C + Y − ] = [Y − ] at [∼A − X + ] > [∼C + Y − ]. This is because there are two different models in PEC formation: , random model (RM) in which the added polyions “uniformly” bind to all of the oppositely charged polyions in the system, and all-or-none model (AONM) in which a part of the polyions in the system “preferably” bind to the added polyions of opposite charge to “entirely” neutralize their electric charges, so that the other part of the polyions in the system remains uncomplexed with the added polyion.…”
Section: Introductionmentioning
confidence: 99%